Customer Loyalty Appraisal Based on Store Characteristics: An Alternative Approach - Chavadi, Chandan A.; Hiremath, Chetan V.; Hyderabad, Raju L. (Indian Journal of Marketing, 2014)
The universal goal of competitive retail business is to gain loyal customers. As the number of stores in the same market area is increasing, each store competes to attract customers to its outlets. The present study makes an attempt to identify factors which can correctly categorize loyal and disloyal customers of the store and to derive a statistical equation which can predict the loyal and disloyal customers of the store. Furthermore, the study identifies decisive factors which need attention to convert disloyal customers into loyal customers. The results indicate that selected factors (merchandize, frequency of sales promotion, ambience, proximity, price, quality of sales staff, and service) have the capability of predicting group membership, that is, loyal or disloyal. Furthermore, the analysis revealed that there is a significant difference in perception of the two groups about all the selected factors except merchandize quality. In addition, the statistical model arrived in the research paper is able to classify customers correctly to the extent of 81.6%. Among the decisive factors, price factor needs top most attention for the store followed by service and others. This research can be used as a guideline to identify loyal and disloyal customers of the store and to improve overall store performance by increasing the customer loyalty base.